Factors affecting survival of foals with pneumonia in a referral hospital - Heini Sofia Rossi; Heli Katariina Hyytiäinen; Jouni Juho Tapio Junnila; Minna Marjaana Rajamäki; Anna Kristina Mykkänen (BMC Veterinary Research)
Abstract Background Pneumonia is a common condition in ailing neonatal foals, and it remains an important cause of morbidity and mortality in this veterinary patient group. Factors affecting the survival of young foals with pneumonia have not been thoroughly investigated. The aim of this study was to explore the potential prognostic factors associated with survival of these foals. Fifty foals under one month of age with pneumonia were included in this retrospective clinical study. The foals were divided into groups based on survival (survived to discharge or died/euthanised during hospitalisation). Multiple clinical and laboratory variables were investigated as risk factors with univariate logistic regression analyses and subsequently with multivariate analyses. If a variable showed prediction potential in regression analysis, a receiver operating characteristic (ROC) analysis was conducted. Results In univariate analysis, odds (OR, 95% CI) of non-survival were associated with higher respiratory rate (RR) on the first day after admission to hospital (D1) (1.32, 1.07–1.62, P = 0.009, for each 5-unit increase) and positive bacterial blood culture (12.08, 1.88–77.67, P = 0.009). Odds of non-survival were decreased for Standardbred breed (0.11, 0.01–0.96, P = 0.046) and for foals with longer hospitalisation, with each additional day in hospital further reducing the odds (0.59, 0.40–0.86, P = 0.006). In multivariate analysis, odds of non-survival were associated only with higher RR on D1 (1.36, 1.07–1.71, P = 0.011, for each 5-unit increase). In ROC analysis, optimal cut-off value for RR was ≥ 55/min with sensitivity 75.0% and specificity 76.3%. Based on predictive values, RR < 55/min on D1 favoured survival. Conclusions Higher RR on D1 is a predictor of non-survival in foals with pneumonia in this study, increasing the odds of death by 36% for each 5-unit increase in RR. Respiratory rate below 55/min on D1 favours survival. These findings could assist in early identification of foals that are at increased risk of mortality, thereby aiding in treatment decisions.